Pengembangan Sistem Informasi Manajemen Proyek Properti Berbasis Website (Studi Kasus: PT. Sona Citra Mandiri) - Citra Nadya Dwi Irianti; Imam Cholissodin; Achmad Arwan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
SONA CITRA MANDIRI is a company engaged in construction services located in Malang. There is a problem, namely the manager project does not have special tools in preparing activities and budget plans, so it is made based on estimates with the help of makeshift tools. This process takes a relatively long time and the quality of the design depends on the experience of the manager project who handles it. Project implementation often experiences a setback in completion of work so that it must experience rescheduling. In implementing a project, the use of labor and material tools can deviate from the plan. The occurrence of construction that is not in accordance with the plan needs attention. Needs analysis was carried out by conducting interviews with related parties, and using literature studies on existing problems. Resulting in 66 functional requirements and 3 non-functional requirements. In addition, the design method uses modeling in UML. The programming language uses the programming language PHP, HTML5, CSS3 and Javascript with the Laravel and Inerty Js framework, as well as the MySQL database. The results of the study showed that there were 66 test scenarios and all of them were successful. In unit testing using themethod white box, testing was carried out by referring to the 3 main functions and obtained 7 test scenarios with all of the results obtained.